Food trade policy and the dietary transition - Martin, Will (OCP Policy Center, 2019)
The irony facing many developing countries today is that increased food trade and the implications of globalization has created a situation where certain segments of the population are simply put, eating too much, while just in their proximity lies a more significant segment of the population who are suffering from the complete opposite, malnutrition. This policy brief aims at explaining this double sided sword.